2013
DOI: 10.1371/journal.pone.0053535
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Protein Interactions between Dengue Fever Virus and Its Hosts, Human and Mosquito

Abstract: The four divergent serotypes of dengue virus are the causative agents of dengue fever, dengue hemorrhagic fever and dengue shock syndrome. About two-fifths of the world's population live in areas where dengue is prevalent, and thousands of deaths are caused by the viruses every year. Dengue virus is transmitted from one person to another primarily by the yellow fever mosquito, Aedes aegypti. Recent studies have begun to define how the dengue viral proteins interact with host proteins to mediate viral replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 164 publications
(207 reference statements)
3
93
0
1
Order By: Relevance
“…In another study, Mairiang et al identified several mosquito protein interacting partners of DENV-2 C, prM, NS3, NS4A, NS4B, and NS5 proteins [23]. Interestingly, the study identified similar proteins that were also identified in our study.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In another study, Mairiang et al identified several mosquito protein interacting partners of DENV-2 C, prM, NS3, NS4A, NS4B, and NS5 proteins [23]. Interestingly, the study identified similar proteins that were also identified in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, the study identified similar proteins that were also identified in our study. These include human ribosomal protein and mosquito carboxypeptidase, which were suggested to interact with the DENV C protein [23]. However, although most of the earlier studies have identified putative interacting partners of DENV proteins, very limited information is available on mosquito protein interactors of DENV E and NS1 proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of approaches have been used to identify NS5-interacting partners (Carpp et al, 2014;Doolittle & Gomez, 2011;Khadka et al, 2011;Le Breton et al, 2011;Mairiang et al, 2013). The yeast two-hybrid system (Y2H) offers the advantage of rapid large-scale screening of protein pairs.…”
Section: Introductionmentioning
confidence: 99%